Psychosexual Development in Men with Congenital Hypogonadotropic Hypogonadism on Long-Term Treatment: A Mixed Methods Study - Andrew A. Dwyer, MSN, FNP-BC; Richard Quinton, MD; Nelly Pitteloud, MD; Diane Morin, PhD (Sexual Medicine, 2015)
Introduction: Congenital hypogonadotropic hypogonadism (CHH) is a rare, genetic, reproductive endocrine disorder characterized by absent puberty and infertility. Limited information is available on the psychosocial impact of CHH and psychosexual development in these patients. Aim: The aim of this study was to determine the impact of CHH on psychosexual development in men on long-term treatment. Methods: A sequential mixed methods explanatory design was used. First, an online survey (quantitative) was used to quantify the frequency of psychosexual problems among CHH men. Second, patient focus groups (qualitative) were conducted to explore survey findings in detail and develop a working model to guide potential nursing and interdisciplinary interventions. Main Outcome Measures: Patient characteristics, frequency of body shame, difficulty with intimate relationships, and never having been sexually active were assessed. Additionally, we collected subjective patient-reported outcomes regarding the impact of CHH on psychological/emotional well-being, intimate relationships, and sexual activity. Results: A total of 101 CHH men on long-term treatment (>1 year) were included for the analysis of the online survey (mean age 37 ± 11 years, range 19–66, median 36). Half (52/101, 51%) of the men had been seen at a specialized academic center and 37/101 (37%) reported having had fertility-inducing treatment. A high percentage of CHH men experience psychosexual problems including difficulty with intimate relationships (70%) and body image concerns/body shame (94/101, 93%), and the percentage of men never having been sexually active is five times the rate in a reference group (26% vs. 5.4%, P < 0.001). Focus groups revealed persisting body shame and low self-esteem despite long-term treatment that has lasting impact on psychosexual functioning. Conclusions: CHH men frequently experience psychosexual problems that pose barriers to intimate relationships and initiating sexual activity. These lingering effects cause significant distress and are not ameliorated by long-term treatment. Psychosexual assessment in CHH men with appropriate psychological support and treatment should be warranted in these patients. Dwyer AA, Quinton R, Pitteloud N, and Morin D. Psychosexual development in men with congenital hypogonadotropic hypogonadism on long-term treatment: A mixed methods study. Sex Med 2015;3:32–41.